JOYFUL LEARNING APPROACH IN INCREASING MOTIVATION TO LEARN ENGLISH IN MIDDLE SCHOOL STUDENTS OF SAN FABIAN, PHILIPPINES - Ida Yeni Rahmawati; Betty Yulia Wulansari; Nurtina Irsad Rusdiana; Ayu Pujiati; Siti Khoirul Bariyah (UIN Alauddin Makassar, 2024)
Joyful learning is a learning approach that prioritizes joy and pleasure in the teaching and learning process. In the context of learning English as a second language, the application of joy learning is expected to increase students' motivation and interest in learning English. This research aims to analyze the implementation of happy learning in learning English as a second language at San Fabian Elementary School, Philippines. This research uses a descriptive qualitative research approach. The data source for this research is the English teacher at San Fabian Elementary School, totaling 1 teacher and 25 students in grade 1 elementary school. Data collection techniques were carried out combined through interviews, observation and documentation. The data analysis technique in this research was carried out by data triangulation. The results of this research state that the implementation of the Joyful Learning approach has brought more positive and enjoyable English learning for students at San Fabian Elementary School, Philippines. This approach not only increases students' understanding of learning material but also increases their learning motivation. With this approach, students can learn English more effectively and have fun. Apart from that, implementing joyful learning can also create a positive and enjoyable learning environment where students can feel comfortable and confident in communicating in English.